Pre-service teachers’ perspective toward problematic word problems - Rafiepour, Abolfazl; Khazaie, Zohreh; Verschaffel, Lieven (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Despite extensive research indicating that students often fail to apply real-world knowledge and common sense when solving word problems, the underlying causes remain underexplored. Teacher behavior and instructional methods are potential factors contributing to students' tendency to provide unrealistic answers to such problems. The current study aims to address this gap by examining the cognitive processes and perspectives of pre-service teachers when solving problematic word problems. A group of 146 pre-service teachers (97 females, 49 males) in Iran participated in the study, which consisted of two phases. In the first phase, participants were given three problematic word problems to solve and were subsequently asked to evaluate four different student responses. A significant correlation was found between the participants' responses in the initial test and their evaluations in the second phase. In the second phase, the study employed a phenomenographic approach to explore the thinking processes and perspectives of the pre-service teachers while solving the problems. The analysis of interview data led to the identification of two primary categories of unrealistic problem-solving: